N-(2-Hydroxyphenyl)-4-nitrophthalimide - Mansor, Shahirah; Zakaria, Norzalida; Ariffin, Azhar; Ng, Seik Weng (International Union of Crystallography, 2008)
Mol-ecules of the title compound, C(14)H(8)N(2)O(5), are linked by a hydr-oxy-amide O-H⋯O hydrogen bond into a linear chain. The hydr-oxy group is disordered over two positions of the benzene ring in an approximate 0.57:0.43 ratio.